The role of Copper (II) in nitrogen metabolism in Mycobacterium tuberculosis - Halicki, Priscila Cristina Bartolomeu; Nazareth, Carolina de Oliveira; Vicenti, Juliano Rosa de Menezes; Ramos, Daniela Fernandes (VITTALLE - Revista de Ciências da Saúde, 2024)
In addition to carbon, nitrogen plays a fundamental role as a constituent of biomolecules such as amino acids, nucleotides, cell wall components and organic cofactors. Compared to carbon metabolism, the acquisition and assimilation processes are used by pathogens to sequester nitrogen from their recently emerged host. Mycobacterium tuberculosis can use multiple nitrogen sources for in vitro growth, including it appears to play the fundamental role in the alkalinization of the intramacrophagic environment ensuring the survival of the bacillus in the host during infection. In addition, copper (Cu), to be considered essential micronutrients has been proposed as an important metal in infection caused by M. tuberculosis, especially as a urease enzyme inhibitor. So, this study evaluated the nitrogen metabolism in the modulation of copper activity in growth kinetics of M. tuberculosis exposed to different nitrogen sources and the minimum inhibitory concentration of copper with and without the presence of these compounds. Considering the sources for the acquisition of nitrogen by M. tuberculosis, there was a change in the growth kinetics when exposed to glutamic acid, urea, L-arginine and ammonium sulfamate. In addition, glutamic acid and urea, despite being the preferred sources of nitrogen for the maintenance of the bacteria, modulate the antimicrobial action of Copper (II), suggesting competition for the site of action between them. In this way, the development of compounds, such as metallic ones, could be an interesting alternative in the development of new therapeutic alternatives with new mycobacterial targets, including against the latent bacillus.